Mīkhāīl Nu’aymah in Arabic Romanticism of Mahjar Literature - Azkia, Wichda Rachma; Anwari, Moh Kanif (Universitas Al Azhar Indonesia, 2024)
The emergence of romanticism was a major revolution against classism, including in Arabic literature. The spread of this school in Arabic literary works was conveyed by the figures of the Diwan school, Apollo, and the Mahjar poets who were influenced by Western romanticism. This article aims to provide an overview of romanticism in the mahjar Arabic literature, especially through Mīkhāīl Nu'aymah’s view as one of the important figures of this stream. The method used in this article is descriptive qualitative and literature study. This research also uses observing and note-taking techniques in data collection. The results of this research show that Nu'aymah's view regarding the school of romanticism is the philosophical basis for the renewal of Arabic literature through the collaboration of Western romanticism and Eastern thought to oppose the classical school. Nu'aymah's mahjar poems represent the romantic characteristics of the mahjar group both in the form and the content of literary works.Keywords – Arabic Romanticism, Mahjar Literature, Mīkhāīl Nu’aymah.